Biometric data in smart cities : methods and models of collective behavior /: methods and models of collective behavior. (2021) - Bilan, Stepan, 1962-; Bilan, Mykola Mykolayovych, 1961-; Motornyuk, Ruslan Leonidovich, 1976-; Yuzhakov, Serhii
No abstract available